PERSEPSI DOSEN AKAN KEPUASAN TERHADAP SISTEM REMUNERASI (Studi pada Dosen di Lingkungan Universitas Brawijaya) - Prasetya, Arik (Profit: Jurnal Adminsitrasi Bisnis, 2017)
The purpose of this research is to know the perception of lecturer on the implementation of remuneration system in Universitas Brawijaya, and to know the description of satisfaction on remuneration system being applied. In this study the selected sample is lecturer at 13 (thirteen) Faculty in Universitas Brawijaya. Sample selection technique using incidental sampling counted 94 lecturers. Technique of collecting data by using Questionnaire, and analyzed by using descriptive statistic analysis. The results of this study indicate that the perception of the lecturer on the remuneration system is generally quite good, but there are still some things that are still lacking, which is related to the understanding of the system of calculation based on the system points imposed due to the lack of socialization.Â Â